The Role of Artificial Intelligence in Developing Hospital Information Management Systems - I Ketut Dian Lanang Triana; Putu Dyah Candra Agustina; Rivaldi Febrian; I Dewa Gede Putra Wiadnya; Vip Paramarta (Universitas Muhammadiyah Yogyakarta, 2024)
Hospital information management systems (HIMS) play significant roles in improving clients' health by applying developed technologies, one of which is artificial intelligence (AI). This study aims to explore the roles of AI in order to support the development of HIMS. We conducted a literature review by extracting the articles from PubMed, ProQuest, and Google Scholar in the past 5 years (January 2019-August 2023) using specific keywords. The full text of relevant articles then thematically synthesized and to be presented. Our findings revealed eight themes that represent the role of AI in supporting the hospital information management system and its implementation in healthcare settings. The themes identified include Diagnosis and Medical Imaging, Health Data Management, Risks Prediction and Disease Progression, Inventory and Procurement Management, Telemedicine and Remote Consultation, Patient Care Management, Drug Development and Clinical Research, and Hospital Data Security System. The AI implementation brings the potential to improve efficiency, accuracy, and quality of care in hospitals. However, it should be noted that the development and implementation of AI need to consider the ethical aspects and proper integration through existing health systems.